Protection and enhancement of surface water bodies to mitigate local flooding : a case study in Hanoi Capital, Vietnam - Pham Quoc Dung; Ranjith Perera; Vilas Nitivattananon; Nguyen, Thi Kim Oanh; Canada (CIDA) (Pathum Thani, Thailand : Asian Institute of Technology, 2010)
With the ons et of fast u rbanization since 1986, after the introduction of the Doi Moi Policy, many surface water bodies in Hanoi city have disappeared . The policies and strategies of the city government have been ineffective or inadequate to protect surface water bodi es . The purpose of this study is to investigate the causative relationship between the attenuation of surface water bodies and increasing local flooding incident s . The investigation is based on the perspective of stakeholders ranging from citizens and city authorities. The study revealed that ineffective planning measure s , lack of awareness of local people and lack of regulation for the protection of surface water bodies as main causative factors for the attenuation of surface water bodies. The study also c onfirms that the flooding incident s and intensity have increased with the decrease of the area of surface water bodies. Based on these findings the study proposes to integrate water bodies as a spatial element in urban plan ning and suggest role s and respon sibilities for stakeholders in protection of surface water bodies in Hanoi.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Urban Env ironmental Management
Thesis (M.Sc.) - Asian Institute of Technology, 2010
Keywords: Floods -- Management -- Vietnam -- Hanoi; Flood control -- Vietnam -- Hanoi